The Status of Coastal Benthic Ecosystems in the Mediterranean Sea: Evidence From Ecological Indicators - Bevilacqua, Stanislao; Katsanevakis, Stelios; Micheli, Fiorenza; Sala, Enric; Rilov, Gil; Sarà, Gianluca; Malak, Dania Abdul; Abdulla, Ameer; Gerovasileiou, Vasilis; Gissi, Elena; Mazaris, Antonios D.; Pipitone, Carlo; et al. (Frontiers in Marine Science, 2020)
The Mediterranean Sea is subject to multiple human pressures increasingly threatening its unique biodiversity. Spatially explicit information on the ecological status of marine ecosystems is therefore key to an effective maritime spatial planning and management, and to help the achievement of environmental targets. Here, we summarized scientific data on the ecological status of a selection of marine ecosystems based on a set of ecological indicators in more than 700 sites of the Mediterranean Sea. For Posidonia oceanica seagrass beds, rocky intertidal fringe and coastal soft bottoms, more than 70% of investigated sites exhibited good to high ecological conditions. In contrast, about 2/3 of sites for subtidal rocky reefs were classified to be in moderate to bad conditions, stressing the need for prioritizing conservation initiatives on these productive and diverse environments. Very little quantitative information for the was available for the southern Mediterranean Sea, thus monitoring programmes and assessments in this area are essential for a representative assessment of the health of marine ecosystems in the whole basin. This overview represents a first step to implement a baseline that, through georeferenced data on ecological status, could help identifying information gaps, directing future research priorities, and supporting improvements to spatial models of expected cumulative impacts on marine ecosystems.